2018
DOI: 10.1111/fcre.12375
|View full text |Cite
|
Sign up to set email alerts
|

What Works in Custody Mediation? Effectiveness of Various Mediator Behaviors

Abstract: This study uses behavioral observation and pre‐and post‐mediation questionnaires to measure the impact of mediator behaviors on participant attitudes and case outcomes in 130 court‐connected custody mediations involving 270 participants and 30 mediators. As a quasi‐experimental design, regression analysis controlled for a broad range of participant attitudinal and case characteristics. Mediator reflecting and eliciting strategies were associated with positive outcomes, while directing strategies had significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 17 publications
1
20
0
2
Order By: Relevance
“…A behavioral observation study of courtconnected custody mediations found that mediators' greater use of reflecting strategies (to identify emotions, values, and issues expressed by the parties) decreased settlement but increased parties' reports of improved understanding of and relationship with the opposing side (Charkoudian, Walter, & Eisenberg, 2018). Most of these studies have been in family mediation rather than small claims settings.…”
Section: Relational Strategiesmentioning
confidence: 99%
See 4 more Smart Citations
“…A behavioral observation study of courtconnected custody mediations found that mediators' greater use of reflecting strategies (to identify emotions, values, and issues expressed by the parties) decreased settlement but increased parties' reports of improved understanding of and relationship with the opposing side (Charkoudian, Walter, & Eisenberg, 2018). Most of these studies have been in family mediation rather than small claims settings.…”
Section: Relational Strategiesmentioning
confidence: 99%
“…In the long term (6 months later), reflecting strategies were associated positively with an increase in parties' willingness to consider the other parent's perspective, prioritization of their children's needs, and desire to have a positive relationship with the other parent (Charkoudian et al, 2018). Mediators' eliciting ideas or solutions from the parties had a positive effect on settlement in a behavioral observation study of custody mediations (Charkoudian et al, 2018). Joint problem solving between disputants during mediation has been associated with improved long-term relationships approximately 4 to 8 months later, even after controlling for the level of hostility between the parties (Pruitt, Peirce, McGillicuddy, Welton, & Castrianno, 1993).…”
Section: Relational Strategiesmentioning
confidence: 99%
See 3 more Smart Citations